Effects of Calliandra and Sesbania on Daily Milk Production in Dairy Cows on Commercial Smallholder Farms in Kenya. (21st February 2020) - Makau, D. N.; VanLeeuwen, J. A.; Gitau, G. K.; McKenna, S. L.; Walton, C.; Muraya, J.; Wichtel, J. J.
Abstract : There is a growing interest in protein supplementation of dairy-cow diets using leguminous shrubs. The study objective was to ascertain the association between diet supplementation with Calliandra calothyrsus and Sesbania sesban and milk production in dairy cattle on commercial smallholder farms. This trial involved 235 cows from 80 smallholder dairy farms in Kenya randomly allocated to 4 intervention groups: (1) receiving Calliandra and Sesbania and nutritional advice; (2) receiving reproductive medicines and advice; (3) receiving both group 1 and 2 interventions; and (4) receiving neither intervention. Farm nutritional practices and management data were collected in a questionnaire, and subsequent physical examinations, mastitis tests, and milk production of cows on the farm were monitored approximately monthly for 16 months. Descriptive and univariable statistical analyses were conducted, and multivariable mixed-model regression was used for identification of factors associated (P < 0.05 ) with daily milk production. The mean milk production was 6.39 liters/cow/day (SD = 3.5). Feeding Calliandra/Sesbania to cows was associated (P < 0.0005 ) with an increase in milk produced by at least 1 liter/cow/day with each kg fed. Other variables positively associated with ln daily milk production in the final model included feeding of Napier grass, amount of silage and dairy meal fed, body condition score, and appetite of the cow. Other variables negatively associated with ln daily milk production in the final model included amount of maize germ fed, days in milk, sudden feed changes, pregnancy, and subclinical mastitis. In conclusion, our field trial data suggest that use of Calliandra / Sesbania through agroforestry can improve milk production in commercial smallholder dairy farms in Kenya. Agroforestry land use systems can be adopted as a way for dairy farmers to cope with feed shortages and low crude protein in farm-available feeds for their cows.